Ultrasound and enzymatic mediated extraction of vitexin and isovitexin from ficus deltoidea leaves - Nur Aima Syairah, Mohd Abdul Alim (2017)
Ficus deltoidea or ‘Mas Cotek’ is regarded as one of the most precious herb plants in Malaysia due to its content of beneficial active compounds and appreciation as a traditional remedy. This research focused on the investigation of the performance of ultrasound using three sonication duty cycle regimes: 10%, 20% and 40% at an intensity of 8.66 W/cm2 in the extraction procedure of active compounds from F. deltoidea leaves by the implementation of both ultrasound and enzyme to determine the sonication regiments and their mechanism reactions that might be suitable to improve the productivity of extraction comparatives to control. It is also focus on the identification of active compounds that present in the leaves of F. deltoidea, especially of vitexin and isovitexin. Due to the availability and abundancy of active compounds, female leaves of F. deltoidea were chosen to be used in this study. The optimum yield recorded for vitexin compound was 1.067 ± 0.001 (%w/w) from; 1:10 (g/mL) sample-to-water ratio, 50 °C temperature, 10% duty cycle, 0.4% enzyme concentration at 3rd hour of extraction. While for isovitexin compound, the optimum value recorded was 0.374 ± 0.028 (%w/w) from; 1:20 (g/mL) sample-to-water ratio, 50 °C temperature, 10% duty cycle at 3rd hour of extraction. The morphological characterization of the extracted dried leaves particles performed using FE-SEM showed a slight ruptures and more voids on the surface of ultrasound-assisted and enzymatic-mediated extraction sample when compared to conventional extracted sample. The experimental values under best conditions were in good consistent with the predicted values, which suggested that sonication and enzymatic treatment are more efficient process in comparison to conventional boiling extraction. The improvement on the extraction method using ultrasound and enzymatic approaches in the present study should be extended to the identification of more phenolic compounds from various parts of F. deltoidea plants and serves as key information for larger scale study in the future work.